Unusual Foreign Body of Pancreas: Surgical Management - Yadav, Thakur Deen; Singh, Harjeet; Sah, Rakesh (JOP. Journal of the Pancreas, 2013)
Context The foreign ingestion is common occurrence but migration to pancreas is rare entity. Most of foreign bodies pass spontaneously through the anus but about 1% can perforate the wall of stomach or duodenum to reach solid organ. Pancreatic foreign body can results in fatal complication. Pancreatic foreign body can be removed endoscopically or surgically. Case report We are reporting a case of successful removal of pancreatic foreign body (sewing needle) by surgery. Conclusion Pancreatic foreign body is a uncommon entity and surgical removal is warranted in majority of cases. Image: Local resection of a needle bearing part of head pancreas.